2022
DOI: 10.1097/mpa.0000000000002064
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Clinical Backgrounds and Malignant Progression of Suspected Intraductal Papillary Mucinous Neoplasm

Abstract: Objectives: Some intraductal papillary mucinous neoplasms (IPMNs) have malignant potential and can become pancreatic cancer. The mechanism behind the malignant progression of IPMN remains unknown. We aimed to identify the risk factors and interactions between backgrounds for IPMN. Methods:We retrospectively enrolled 980 patients of pancreatic cancer or suspected IPMN (sIPMN) who underwent endoscopic ultrasound or retrograde cholangiopancreatography. We classified them into pancreatic cancer, high-risk sIPMN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 32 publications
1
1
0
Order By: Relevance
“…reported that smoking may accelerate the development of IPMN and the subsequent transformation into invasive cancer ( 64 ). The role of smoking was also reported in a Japanese population, in agreement with our observation in Europeans ( 65 ). In pancreatic cancer, the molecular mechanisms of cigarette smoking are currently unknown; however, a synergic role of nicotine metabolites and rare mutations (i.e., KRAS mutations) has been proposed.…”
Section: Discussionsupporting
confidence: 92%
“…reported that smoking may accelerate the development of IPMN and the subsequent transformation into invasive cancer ( 64 ). The role of smoking was also reported in a Japanese population, in agreement with our observation in Europeans ( 65 ). In pancreatic cancer, the molecular mechanisms of cigarette smoking are currently unknown; however, a synergic role of nicotine metabolites and rare mutations (i.e., KRAS mutations) has been proposed.…”
Section: Discussionsupporting
confidence: 92%
“…Limited and delayed diagnostic strategies increase the difficulty of diagnosis, thus severely impeding various therapeutic options. Although increasing evidence suggests that pancreatic cancer is linked to several variables, such as smoking, alcohol consumption, coffee intake, a high-fat and protein diet, and genetic background (3)(4)(5), the causes of pancreatic cancer remain unknown.…”
Section: Introductionmentioning
confidence: 99%